Relationship Between D-Dimer, Albumin Levels, and Outcome of COVID-19 Patients at Dr. M. Djamil General Hospital, Padang - Wahyudin, Hendris Utama Citra; Khairsyaf, Oea; Russilawati, Russilawati (Indonesian Society of Respirology (ISR), 2024)
Background: Several studies have found an increase in D-dimer levels in patients who died from a severe clinical condition. COVID-19 exhibits multi-organ dysfunction through several markers, including decreased albumin levels. There were some studies that were interested in understanding how D-dimer and albumin levels relate to the outcomes of COVID-19 patients. The aim of this study was to investigate the relationship between D-dimer, albumin levels, and patient outcomes. Method: This was a cross-sectional study of all COVID-19 patients treated at Dr. M. Djamil General Hospital, Padang, from January 1st, 2021 to December 31st, 2021. Results: The majority of patients (40.71%) were in the group of 18 and 49 years old; more than half of the subjects (56.16%) were female; and obesity was the most common comorbidity (40.9%). The majority of the subjects (42.79%) had moderate clinical COVID-19. Higher D-dimer levels had a statistically significant independent relationship with unfavorable outcomes (P=0.0001). Lower albumin levels had a statistically significant independent relationship with unfavorable outcomes (P=0.0001). Higher D-dimer and lower albumin each contributed 12.6% to patient outcome. Increasing D-dimer levels per 1 ng/mL would increase the probability of an unfavorable outcome by 0.120 times, and on the other hand, increasing albumin levels per 1 g/dL would increase the probability of survival by 2.143 times. Conclusion: Higher D-dimer levels independently had a relationship with an unfavorable outcome. Higher albumin levels were independently related to a favorable outcome.